Knowledge portals in contemporary organizations - Fernández Morales, Mynor (2014)
This essay deals with the importance of a knowledge portal as a tool for the systematic management and harmonious growth of an organization, since it is a technical and management tool which contemporary organizations should have to compete better in an increasingly globalized and post-industrial society where the main competitive advantage is undoubtedly knowledge. Emphasis is given to aspects of administrative nature rather than technical, to introduce the portal as a management tool that facilitates knowledge management. Its consolidation and good success depend on the existence of a collaborative environment among information professionals in the systematic management of organizational knowledge.